An A-Team approach to learning classifiers from distributed data sources. (12th July 2010) - Czarnowski, Ireneusz; Jedrzejowicz, Piotr; Wierzbowska, Izabela
Distributed data mining is an important research area. The task of distributed data mining is to analyse data from different sources. Solving such tasks requires special approaches and tools, different from those dedicated to analysing data located in a single database. This paper presents an approach to learning classifiers from distributed data that is based on data reduction (the prototype selection) at the local level. In such case, the aim of data reduction is to obtain a compact representation of distributed data repositories that include non-redundant information in the form of so-called prototypes. The approach has been implemented using the JABAT environment, which, in turn, is an implementation of the A-Team concept. The paper includes a general overview of JABAT, the problem formulation and a description of the proposed solution in which the global classifier is induced from prototypes that are selected from distributed datasets in the process of data reduction at the local level. Finally, computational experiment results validating the approach are shown. The experiment results indicate that proposed classifier can produce very good classification results.